ANALISIS HUBUNGAN FINANCIAL PERFORMANCE DAN CORPORATE SOCIAL RESPONSIBILITY - Doni Kurniawansyah; Siti Mutmainah (Diponegoro Journal of Accounting, 2013)
The aims of this research are to know the relationship between financial performance and corporate social responsibility in the Indonesian banking sector. Corporate Social Responsibility is company’s activities that its operations based on the aspects of economic, social and environment. In this study, financial performance is measured by used the  capital adequancy ratio (CAR), non performing loan (NPL), return on assets (ROA) and  loan to deposit ratio (LDR). This study used two test models, the first model used the financial performancet as the independent variable and corporate social responsibilityt+1 as the dependent variable. In the second model, corporate social responsibilityt are used as independent variables, financial performancet+1 is used as the dependent variable.            Banking companies used in this research are all banking companies listed in 2009-2011. Limited of listed companies, thus using the entire census listing companies by 29 companies. The method of analysis used in this study was multiple regression.             Based on the test results, the first model was found that the NPL and LDR  variable was not significant at the 5% significance level, but at the 10% significance level, the variables NPL has significant negative effect and LDR has significant positive effect on CSR. Meanwhile, CAR and ROA variables has no effect on CSR. In the second model, it was found that the variable CSR has positive significant effect on the variable ROA. Meanwhile, CSR does not affect the variable LDR at the 5% significance level, but at the 10% significance level, the variable CSR has significant positive effect to LDR. CSR does not affect the variable CAR and NPL.